Dislocation and continuity: Marking the 30th anniversary of the Catholic Bishops" pastoral letter Living Our Faith - Mpofu, Buhle (HTS teologiese studies, 2022)
One of the reasons that prompted Malawi’s Catholic bishops to write a pastoral letter in 1992 that triggered the movement towards democracy was the big gap between the rich and the poor. The pastoral letter, Living Our Faith, emerged as a critical voice in challenging the socio-economic and political state of affairs. The bishops demanded that the government ensures fair distribution of wealth. Since that time, Malawi has experienced different political parties that have assumed state governance after promising to eradicate poverty in their campaign manifestos. Despite political changes, Malawi continues to experience the very same challenges, which prompted the Catholic bishops to write the pastoral letter in 1992. This contribution drew on the notions of dislocation and discontinuity to explore the significance of the pastoral letter towards commemorating the 30th anniversary of this historical event in Malawi. Living Our Faith marked the end of one-party dictatorial regime and the beginning of a multiparty system of governance, something to be celebrated as dislocation. This research interrogated the custodianship of the 1992 Catholic bishops’ pastoral letter and suggested that intellectuals should facilitate socio-political and economic transformation and demonstrated the relevance of the pastoral letter as a blueprint for socio-economic transformation in Malawi.Contribution: This research contributes to the evaluation of progress in the role played by the Church and intellectuals in the development of Malawi.